Is it time to cut the gordian knot of polar sovereignty? - Jabour, J; Weber, M (Review of European Community & International Environmental Law, 2008)
There has been recent discussion on the abandonment ofsovereignty in the Arctic and territorial and marineclaims in Antarctica in the interests of redefining theseregions into global commons with joint management.Global commons refers to a region, or group of valuedresources, protected from exploitation in the interestsof the global population and future generations. Whileit may be reasonable to examine the possibility ofshifting sovereignty in these regions and locking accessto any of the resources, an academic examination mustnot focus on sovereignty in isolation from existingmanagement regimes. Sovereignty is not displacedeasily, and nor are sovereign rights; however there isa large capacity for negotiation, consent and agreementtowards how resources and areas may be usedand enjoyed while maintaining an indifference toexisting or exerted territorial and/or marine claims.Sovereignty and sovereign rights can also be preserved,but their utility minimized in the presence of alternativearrangements, as exemplified in the Antarctic Treaty.In the absence of such arrangements, the self-interestof States is manifest. A false sense of probability isfostered by any examination that only considerssovereignty and disregards State practice or currentmanagement initiatives. This article demonstratesthat the current governance arrangements are legitimatein a dynamic world, regardless of sovereignty,and identifies the lengths to which the stakeholdersgo to preserve both their national interest and that ofthe global community in de facto global commonsareas. It concludes by offering a view that cutting theGordian knot of polar sovereignty is both risky andpremature in the absence of suitable alternatives.